2008
DOI: 10.1016/j.jtbi.2008.05.028
|View full text |Cite
|
Sign up to set email alerts
|

The role of genetic biases in shaping the correlations between languages and genes

Abstract: It has recently been proposed (Dediu, D., Ladd, D.R., 2007. Linguistic tone is related to the population frequency of the adaptive haplogroups of two brain size genes, ASPM and Microcephalin. Proc Natl Acad Sci USA 104, 10944-10949) that genetically coded linguistic biases can influence the trajectory of language change. However, the nature of such biases and the conditions under which they can become manifest have remained vague. The present paper explores computationally two plausible types of linguistic acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 25 publications
1
37
0
Order By: Relevance
“…ASPM is also a highly accelerated region that holds key features that make us human [112], including perhaps language [180][182]. Deficits in ASPM's functions has been consistently associated with neurodevelopmental disorders, primary in microencephaly [183][188].…”
Section: Resultsmentioning
confidence: 99%
“…ASPM is also a highly accelerated region that holds key features that make us human [112], including perhaps language [180][182]. Deficits in ASPM's functions has been consistently associated with neurodevelopmental disorders, primary in microencephaly [183][188].…”
Section: Resultsmentioning
confidence: 99%
“…I also have used two types of computational agents, Bayesian (sampler and maximizers) and non-Bayesian (implementing two types of biases: initial expectation representing an asymmetric initial state and rate of learning representing an asymmetric easiness of acquisition). The simulations showed that Bayesian agents in situations 2 and 3 still produce language influenced by their biases but in a much more complex manner (Dediu 2009) and that non-Bayesian agents implementing a rate of learning bias also show bias amplification even in scenario 3 (Dediu 2008).…”
Section: Genetic Biasing Of Language At the Population Levelmentioning
confidence: 99%
“…The generalizability of such simple models has been questioned both on grounds of the social and communicative structures considered (Dediu 2008(Dediu , 2009) as well as in the assumptions behind this Bayesian model of language acquisition and usage (Dediu 2009;Ferdinand and Zuidema 2009). To study the effects of more complex (and realistic) social and communicative settings, I have recently conducted a series of studies (Dediu 2008(Dediu , 2009) where computational agents learn and transmit language either in (1) the simple, single-agent transmission chain discussed above; (2) a more complex setting involving chains of pairs of agents (allowing vertical, horizontal, and oblique transmission); and (3) a two-dimensional world with complex demography, featuring several populations that migrate and interact.…”
Section: Genetic Biasing Of Language At the Population Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…By demonstrating that the hypothesised link was stronger than competing hypotheses, a convincing claim was made for the further experimental investigation of this hypothesis. In order to develop the basis of the general theory, a follow-up experimental study found support for part of the hypothesis in that there are individual differences in the perception of pitch [21], and a computer simulation demonstrated that such differences could influence linguistic structure in the long-term [22].…”
Section: Nomothetic Studiesmentioning
confidence: 99%